The Drivers of Public Sector Pension Reform Across the U.S. States. (May 2017) - Thom, Michael
This study analyzes the diffusion of public sector pension reforms across the American states between 1999 and 2012, a policy area notable for its fiscal implications as much as its recent political polarization. Previous enactment in other, non-contiguous states was the largest and most consistent driver of reform. Otherwise, empirical findings suggest that reform antecedents varied by reform type. Existing funding levels reduced the likelihood that states would cut benefits, change pension governance, or reduce cost of living allowances, but had no effect otherwise. Evidence for partisan legislative influence is weak, although Republican control had partial, positive effects on the enactment of pension governance reforms and increases to the retirement age. Across the board, other relevant factors such as constitutional pension protections, collective bargaining rights, and union membership density had no effect. That external contagion pressures have a more robust influence than endogenous conditions raises questions about the future efficacy of pension reform.